PENGARUH PEMAHAMAN INTERNET, SISTEM E-FILLING, DAN TAX KNOWLEDGE TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK PADA KARYAWAN PT. KREASI MAS TERANG MAKMUR - Dila Angraini; Thina Thristyanah Suteja (Jurnal Riset Akuntansi Politala, 2023)
This study aims to determine and analyze the effect of internet understanding, e-filling systems, and tax knowledge on taxpayer compliance of employees of PT. Kreasi Mas Terang Makmur. This study uses primary data obtained from questionnaire data distributed to taxpayer respondents. The sampling technique used purposive sampling. The analysis technique uses multiple linear regression analysis using SPSS version 26 with a significance level of 5%. The results of this study indicate that internet understanding, e-filling system, and tax knowledge variables affect the taxpayer compliance of employees of PT. Kreasi Mas Terang Makmur. Partially understanding the internet does not affect on taxpayer compliance, while the e-filling system and tax knowledge affect PT. Kreasi Mas Terang Makmur.